Servicio al cliente de la empresa haz@net de la Parroquia San Juan. - Córdova Apupalo, Nathaly Dayanara (2022)
This research is based on the customer service of the Haz@net company, an entity dedicated to providing internet service in the San Juan parish and surrounding areas. The institution has been in the market for about seven months, where it has presented a welcome that significantly benefits the rise to the position among the best entities that provide high-speed connectivity in the locality. Despite the acceptance and the high number of users who come to sign contracts with the organization, having consumers completely satisfied is quite a complicated task for the organization due to the high levels of competitiveness in the area. The current case exposes the levels of dissatisfaction of the clients of the company Haz@net regarding the internet service it provides, demonstrating the main factors that decrease the preference in the locality of the institution in question. Through a descriptive-analytical investigation, the situations or shortcomings perceived by the users are presented, through the use of information collection techniques and instruments such as questionnaires, interviews and surveys directed towards the owner manager and consumers respectively.